Liver Structure in Rats with Experimental Hepatic Failure Following Implantation of Macroporous Carrier Seeded with Cryopreserved Fetal Liver Cells - Gritsay, Dmitriy V.; Lebedinskiy, Alexander S.; Ochenashko, Olga V.; Petrenko, Yuriy A.; Volina, Viktoriya V.; Volkova, Natalya. A.; Petrenko, Alexander Yu. (Problems of Cryobiology and Cryomedicine, 2014)
The study demonstrates the state of bioconstructs based on cryopreserved fetal liver cells (FLC), seeded into macro-porous alginate-gelatin matrices (AGM), as well as the effect of the bioconstructs implantation on the liver structure in hepatic failure rat models. As carriers for rat FLC the wide-porous cryogel AGM were applied. The additional alginate capsule formed around the AGM prevented the colonization of matrices by the recipient cells in vivo and did not affect the viability and expansion of FLC in vitro. The structure of bioconstructs was maintained during at least 28 days post implantation. The experimental liver damage in rats was modeled by the injection of the hepatocyte proliferation inhibitor 2-acetylaminofluorene together with the partial hepatectomy, that led to pronounced changes in liver structure (disorderin of trabecular structure of the parenchyma and ductular reaction within the portal and periportal areas). The implantation of FLC-seeded AGM additionally covered by the alginate shell into greater omentum of rats with hepatic failure led to organotypic recovery of pathologically altered liver structure. It was shown that the alginate capsule around the AGM provided isolation for seeded cells, and FLC within the wide-porous AGM had a therapeutic effect when implanted in rats with liver failure. Probl Cryobiol Cryomed 2014; 24(4):292-301.